Anti‐IL‐2R blockers comparing with polyclonal antibodies: Higher risk of rejection without negative mid‐term outcomes after ABO‐incompatible kidney transplantation. Issue 10 (8th September 2019) - Del Bello, Arnaud; Divard, Gillian; Belliere, Julie; Congy‐Jolivet, Nicolas; Lanfranco, Luca; Ricard, Régine; Delas, Audrey; Colombat, Magali; Esposito, Laure; Hebral, Anne‐Laure; Cointault, Olivier; Lefaucheur, Carmen; et al.
Abstract: There is no recommendation regarding the type of induction therapy to use in ABO‐incompatible (ABOi) kidney transplantation. The aim of this retrospective study was to compare the outcome of ABOi living donor kidney transplant (LDKT) recipients who received either polyclonal antibodies or anti‐interleukin‐2 receptor (IL‐2R) blockers as an induction agent. All ABOi HLA‐compatible patients that received a LDKT between 03/11 and 03/18 in three French transplantation center (Paris Saint‐Louis, Paris Necker, and Toulouse) were included in the study. Fifty‐eight patients were given polyclonal antibodies and 39 patients received anti‐IL‐2R blockers. We identified by a Cox proportional hazard model the use of polyclonal antibodies as a protective factor against acute rejection (HR = 0.4, 95%CI [0‐0.9], P < .05). However, pathological findings on protocol biopsies at 1 year were similar in both groups, as were patient and graft survivals, renal function, and complications. We conclude that the acute rejection rate was significantly higher in patients given anti‐IL‐2R blockers compared to polyclonal antibodies. However, in our series, there was no negative impact on mid‐term outcome.